Estudio de la relación entre la conducción de vehículos motorizados y el tiempo de recuperación al deslumbramiento (fotoestrés) en adultos de la Universidad Antonio Nariño Sede Bogotá (2023)
One of the main causes of difficulty in driving is glare, which is defined as a secondary decrease in visual acuity to exposure of the eyeball to intense light, which produces discomfort, fatigue and discomfort in good visual performance